(3eHGOF GdeMGSHI GdeGdjIs - (3eMeO SejQ(B, (3GdUHGfs; (3eMeO YHGS(B, (3HOhjs ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2006)
(3GdeMGSHI Yf YedjGJ GdeTQhY GdUfGYj GdLQO h GdJShjGJ GdLQOjI ddGUhd GdKGHJI , LQO h Jbjje GdeNRhf GdSdYj , GdYedGA , GdjhejGJ GdNGUI h GdMSGHGJ GdeSGYOI GdGLeGdjI h CNjQG JMdjd GdbhGFe GdeGdjI HGSJNOGe GdfSH(B.s
Keywords: (3GdeGdjIs; (3GdeMGSHIs